Ursolic acid enhances stress resistance, reduces ROS accumulation and prolongs life span in C. elegans serotonin-deficient mutants. Issue 5 (17th February 2021) - Naß, Janine; Abdelfatah, Sara; Efferth, Thomas
Abstract : UA acts through serotonin receptors to enhance stress resistance and prolong life span in C. elegans . Abstract : Introduction : Depression and anxiety disorders contribute to the global disease burden. Ursolic acid (UA), a natural compound present in many vegetables, fruits and medicinal plants, was tested in vivo for its effect on (1) enhancing resistance to stress and (2) its effect on life span. Methods : The compound was tested for its antioxidant activity in C. elegans . Stress resistance was tested in the heat and osmotic stress assay. Additionally, the influence on normal life span was examined. RT-PCR was used to assess possible serotonin targets. Results : UA prolonged the life span of C. elegans . Additionally, UA significantly lowered reactive oxygen species (ROS). Molecular docking studies, PCR analysis and microscale thermophoresis (MST) supported the results that UA acts through serotonin receptors to enhance stress resistance. Discussion : Considering the urgent need for new and safe medications in the treatment of depression and anxiety disorders, our results indicate that UA may be a promising new drug candidate.